(untitled) (Journal of Organizational Psychology, 2022)
Using expectancy violation theory as a framework, it was proposed that men and less attractive male and female targets violate the schema people hold regarding workplace sexual harassment, resulting in them being perceived as experiencing less severe harassment, being less believed, and being recommended to pursue less assertive actions. Australian workers (N = 361) aged 18–82 years completed an online questionnaire based on a hypothetical sexual harassment scenario. The findings demonstrated that expectancy violation effects were present, negatively affecting targets who did not meet the schematic norm of a sexual harassment victim, thus highlighting the difficulty and barriers associated with making and assessing organizational sexual harassment claims.